Rapid evolution rescues hosts from competition and disease but—despite a dilution effect—increases the density of infected hosts. Issue 1868 (6th December 2017) - Strauss, Alexander T.; Hite, Jessica L.; Shocket, Marta S.; Cáceres, Carla E.; Duffy, Meghan A.; Hall, Spencer R.
Abstract : Virulent parasites can depress the densities of their hosts. Taxa that reduce disease via dilution effects might alleviate this burden. However, 'diluter' taxa can also depress host densities through competition for shared resources. The combination of disease and interspecific competition could even drive hosts extinct. Then again, genetically variable host populations can evolve in response to both competitors and parasites. Can rapid evolution rescue host density from the harm caused by these ecological enemies? How might such evolution influence dilution effects or the size of epidemics? In a mesocosm experiment with planktonic hosts, we illustrate the joint harm of competition and disease: hosts with constrained evolutionary ability (limited phenotypic variation) suffered greatly from both. However, populations starting with broader phenotypic variation evolved stronger competitive ability during epidemics. In turn, enhanced competitive ability—driven especially by parasites—rescued host densities from the negative impacts of competition, disease, and especially their combination. Interspecific competitors reduced disease (supporting dilution effects) even when hosts rapidly evolved. However, this evolutionary response also elicited a potential problem. Populations that evolved enhanced competitive ability and maintained robust total densities also supported higher densities of infections. Thus, rapid evolution rescued host densities but also unleashed larger epidemics.